PIMENTA DIOICA LEAF EXTRACT USED IN THE SYNTHESIS OF SILVER NANOPARTICLES: CHARACTERIZATION AND EVALUATION OF ANTIMICROBIAL APPLICATIONS - TIWARI, ABHISHEK PRAKASH; TIWARI, RAJKAMAL; YADAV, BAL CHANDRA (Journal of the Inland Fisheries Society of India, 2024)
Green synthesis approaches for the synthesis of nanomaterials and their different uses have been researched and garnered the interest of researchers in recent years (1-5). One excellent instrument for the introduction and advancement of nanotechnology is the green synthesis of noble metal nanoparticles. Because no hazardous or toxic chemicals are used during the plant-mediated synthesis process, also known as phytosynthesis, it is sometimes referred to as "green synthesis" (6, 7). In order to control the morphology, size, and stability of synthesised nano-sized structures, metallic nanoparticles can be prepared using a variety of synthesis techniques, including biological, physical, chemical, and others. However, the most intriguing synthesis method is the one for green metallic anoparticle synthesis. Plant extract-based green synthesis techniques have gained a lot of attention because they are both economical and environmentally friendly (8-10) and because a variety of abundant and diverse biomolecules function as reducing and capping agents (11, 12). Modifying the morphology, shape, size, surface to volume ratio, and composition of nanoparticles (NPs) is a crucial step towards achieving improved physical, chemical, and biological properties for desired applications in various fields, including electronics, household appliances, cosmetics, agriculture, and pharmaceuticals (13-17). Green synthesis methods facilitate this process. The safe and environmentally benign character of phytosynthesized silver nanoparticles (Ag NPs) makes them an attractive option for usage in a wide range of applications. Researchers are constantly looking for less dangerous, manageable, effective, large-scale manufacturing, and environmentally friendly synthesis techniques for nanotechnology advancements and their effects on biological things (18-21). Ag NPs are among the metals that have drawn the most attention from researchers because of their unique physiochemical characteristics and exciting potential uses in biomedicine (22-27). In order to lessen microbial contamination, the scientific community is making use of silver nanoparticles (Ag NPs) in nanomedicine and in combination with other biomaterials. Because of these nanoparticles’ surface plasmon resonance feature, they have also been investigated for bio-imaging applications (28).